2015
DOI: 10.1007/s00300-015-1837-2
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of reproductive biology of wild-caught polar cod (Boreogadus saida) from Svalbard waters

Abstract: Polar cod (Boreogadus saida) is considered a key species in the Arctic marine ecosystems. Yet detailed or even basic knowledge regarding its biology and adaptations, especially during the polar night, is in many cases poor. Data are presently unavailable in Western literature on the gonad development of polar cod and its reproductive biology in wild specimens. Accordingly, gonad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Hernandez et al (2013) found Atlantic cod grunts throughout the 24-hour period but they were more prevalent during daylight hours. Arctic cod are believed to breed under ice between January and April and this season corresponds to the Polar night (Nahrgang et al, 2016), so diel patterns are unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…Hernandez et al (2013) found Atlantic cod grunts throughout the 24-hour period but they were more prevalent during daylight hours. Arctic cod are believed to breed under ice between January and April and this season corresponds to the Polar night (Nahrgang et al, 2016), so diel patterns are unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the life history strategies of polar cod is essential not only for our ability to predict ecological consequences of environmental change in the Arctic, but also for our general understanding of life history adaptations to pronounced seasonality. For polar cod, some life cycle data exist; the species reaches a maximum age of 7-8 years and becomes sexually mature between the age of 2-3 years (Hop and Gjøsaeter 2013), although some specimens may reach maturity at age 1 (Nahrgang et al 2016). Furthermore, males may reach maturity at a younger age and have a shorter life span (Nahrgang et al 2014).…”
Section: Life Cycle Strategiesmentioning
confidence: 99%
“…Furthermore, males may reach maturity at a younger age and have a shorter life span (Nahrgang et al 2014). Recent studies suggest that polar cod is an iteroparous species (Hop et al 1995;Nahrgang et al 2014) with strong indication of a group-synchronous oocyte development with determinate fecundity (Nahrgang et al 2016). Polar cod is assumed to be a pelagic broadcast spawner, producing large floating eggs (Aronovich et al 1975;Graham and Hop 1995), with spawning reported mainly between January and March (Andriyashev 1954;Rass 1968;Ponomarenko 2000).…”
Section: Life Cycle Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Korshunova (2012) collected polar cod by bottom trawling in the western fjords (Isfjord and Billefjord) of Svalbard from August to January and found mature polar cod that had spawned at least once or that were preparing for their first spawning in the coming winter. This study has been supplemented by observations from other fjords (western: Adventsfjorden, Kongsfjorden and Bellsund and northern: Hinlopen and Rijpfjorden), where mature polar cod ages 1-3 were found (Nahrgang et al 2016). However, no spawning has been observed in the area, most likely due to ice coverage and generally minimal survey effort.…”
Section: Introductionmentioning
confidence: 99%